Mercury (II) sensors using Co\(_3\)O\(_4\) fabricated electrochemical method - Nguyen Quoc, Dung; Bui, Dang Quang; Trieu, Thi Anh; Lam, Van Nang; Dang, Van Thanh; Nguyen, Van Truong; Tran, Dai Lam (Communications in Physics, 2025)
A simple and rapid electrochemical method has been developed for the synthesis of Co₃O₄ material via electrochemical deposition on an ITO substrate for use as a sensor electrode for mercury (II) detection. The morphology and structure of the Co₃O₄ were characterized using SEM, EDX, and XRD, revealing a nanosheet structure of the material. The synthesis conditions of the material were systematically investigated. The sensor properties of the fabricated electrode, evaluated using differential pulse anodic stripping voltammetry (DP-ASV), demonstrated a linear detection range for Hg(II) ions from 0.1 to 12 µM, with a sensitivity of 14.559 µA cm⁻¹ µM⁻¹ and a detection limit of 0.06 µM.